2011
DOI: 10.1186/1471-2407-11-444
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency ultrasound for intraoperative margin assessments in breast conservation surgery: a feasibility study

Abstract: BackgroundIn addition to breast imaging, ultrasound offers the potential for characterizing and distinguishing between benign and malignant breast tissues due to their different microstructures and material properties. The aim of this study was to determine if high-frequency ultrasound (20-80 MHz) can provide pathology sensitive measurements for the ex vivo detection of cancer in margins during breast conservation surgery.MethodsUltrasonic tests were performed on resected margins and other tissues obtained fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 50 publications
2
41
0
1
Order By: Relevance
“…One report of ultrasound (in a range of 20 to 80 MHz) evaluated 34 samples from 17 patients and found the technique distinguished lobular carcinoma from normal tissue with specificity of 100% and sensitivity of 86%; ductal carcinoma from normal tissue with specificity of 100% and sensitivity of 74%; benign pathologies from cancer with specificity of 80% and a sensitivity of 82%; and fat necrosis from adenoma with specificity of 80% and sensitivity of 100%. 61 A more recent study of 132 patients reported a sensitivity of 44% and a specificity of 94%. This study notes that US may be a better alternative to specimen x-ray in cases of dense breasts, where x-ray has the most difficulty.…”
Section: Ultrasoundmentioning
confidence: 97%
“…One report of ultrasound (in a range of 20 to 80 MHz) evaluated 34 samples from 17 patients and found the technique distinguished lobular carcinoma from normal tissue with specificity of 100% and sensitivity of 86%; ductal carcinoma from normal tissue with specificity of 100% and sensitivity of 74%; benign pathologies from cancer with specificity of 80% and a sensitivity of 82%; and fat necrosis from adenoma with specificity of 80% and sensitivity of 100%. 61 A more recent study of 132 patients reported a sensitivity of 44% and a specificity of 94%. This study notes that US may be a better alternative to specimen x-ray in cases of dense breasts, where x-ray has the most difficulty.…”
Section: Ultrasoundmentioning
confidence: 97%
“…Therefore, an important clinical challenge in PCa management is to devise a rapid and highly accurate method to detect cancerous cells in real time to allow resection of additional periprostatic tissues and reduce cancer recurrence after surgery. Over the last decade, several innovative analytical techniques (5)(6)(7)(8)(9)(10)(11)(12) have been developed to distinguish cancer from benign tissue in various organs. However, none has achieved wide clinical adoption for various reasons including inconvenience, narrow information content, unavailability, poor sensitivity, slowness of adoption, and operating room workflow incompatibility.…”
mentioning
confidence: 99%
“…Ähnlich wie bei der akustischen Auflösung von Gewebeschichten im Ultra- [15]. Neben etlichen Invitro-und In-vivo-Untersuchungen ist eine kleine Studie von Doyle et al [7] weiter erwähnenswert, die an brusterhaltend operierten Mammakarzinompatientinnen eine direkte Korrelation zwischen den HF-Ultraschallmessungen und den Resektionsrändern zeigen konnte. Allerdings sind diese Daten aufgrund der kleinen Fallzahl und existierender Messunsicherheiten noch nicht reif.…”
Section: Optische Kohärenztomographieunclassified